Effects of pitch spatial references on players’ positioning and physical performances during football small-sided games - Coutinho, Diogo (2019)
The aim of this study was to identify the effects of adding spatial references during football small-sided games in youth players' tactical and physical performance. Twelve under-15 players performed a Gk+ 6v6+ Gk game under two playing conditions: (i) without spatial references (CONTROL condition); (ii) with spatial references, by dividing equally the pitch into three corridors and three sectors (experimental situation, LINES). Players' positional data was used to compute time-motion and tactical-related variables. The results revealed that performance under LINES situation increased the regularity in the zones occupied (~14%, Cohen's d: 0.5; ±0.3; p = 0.003) and in the distance between teammates' dyads (~19%, 0.9; ±0.2; p < 0.001). Oppositely, LINES condition decreased the longitudinal synchronization of players' displacements (0.4; ±0.2; p = 0.002), players' average speed (0.5; ±0.3; p = 0.002) and distance covered at lower (0.9; ±0.3; p < 0.001) and moderate speed (0.5; ±0.3; p < 0.001). Adding spatial references seems to promote a more structured pattern of play and increase positional regularity. However, coaches should be aware that this constraint may decrease the synchronization between players. Overall, these findings may be generalized to most invasion team sports.